Effects of switching from stavudine to raltegravir on subcutaneous adipose tissue in HIV-infected patients with HIV/HAART-associated lipodystrophy syndrome (HALS). A clinical and molecular study. - Pere Domingo; María del Mar Gutierrez; José Miguel Gallego-Escuredo; Ferran Torres; Gracia María Mateo; Joan Villarroya; Ignacio de los Santos; Joan Carles Domingo; Francesc Villarroya; Luis Del Rio; Vicente Estrada; Marta Giralt (PLoS ONE)
HIV-1/HAART-associated lipodystrophy syndrome (HALS) has been associated with exposure to stavudine (d4T) through mitochondrial dysfunction. We performed a 48-week study to assess the effects of switching from d4T to raltegravir (RAL) on metabolic and fat molecular parameters of patients with HALS. Forty-two patients with HALS and a median exposure to d4T > 7 years were switched to RAL and followed for 48 weeks. Fasting metabolic tests, HIV RNA, CD4 cell count, and fat measured by DEXA were obtained at baseline and week 48. mtDNA and gene transcripts for PPAR gamma, adiponectin, cytochrome b, Cox IV, TNF alpha, MCP-1 and CD68 were assessed in paired subcutaneous fat tissue biopsies. Lipid parameters, fasting glucose, insulin, and HOMA-IR did not change significantly. Whole body fat (P = 0.0027) and limb fat mass (P<0.0001) increased from baseline. Trunk/limb fat ratio (P = 0.0022), fat mass ratio (P = 0.0020), fat mass index (P = 0.0011) and percent leg fat normalized to BMI (P<0.0001) improved after 48 weeks. Relative abundance of mtDNA, expression of PPAR gamma, adiponectin, Cyt b, and MCP-1 genes increased, whereas Cox IV, TNF alpha, and CD68 did not change significantly from baseline. Switching from d4T to RAL in patients with HALS is associated with an increase in limb fat mass and an improvement in markers of adipocyte differentiation and mitochondrial function in SAT.